PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS (TGT) BERBANTUAN MEDIA ULAR TANGGA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD: Penelitian kuantitatif eksperimen - yurisa; Gutimal Witri; Muhammad Fendrik (STKIP Subang, 2025)
This study aims to identify and describe the effect of using the Team Games Tournament (TGT) cooperative learning model assisted by snakes and ladders media on the mathematics learning outcomes of fifth-grade elementary school students. The background of this study is motivated by the low mathematics learning outcomes of students, which are caused by the limited variation of teaching methods and the lack of media usage that could enhance student interest and active participation in the learning process. The research method employed is a quasi-experimental design with a non-equivalent control group design. The research sample consists of two classes, namely class VA as the control group and class VB as the experimental group. Data were collected through learning outcome tests, consisting of pretests and posttests. The collected data were analyzed using the Independent Sample T-Test. The results of the study indicate that the average posttest score for the experimental group is 81.25, while the control group obtained an average of 67.92. The statistical test yielded a significance value of 0.005, which is smaller than 0.05, suggesting that there is a significant difference between the mathematics learning outcomes of students taught using the TGT model assisted by snakes and ladders media and those taught using conventional methods. Based on these findings, it can be concluded that the application of the TGT cooperative learning model assisted by snakes and ladders media has a significant positive effect on the mathematics learning outcomes of fifth-grade elementary school students. Therefore, it is recommended that teachers consider the use of this model and media to enhance students' learning outcomes in mathematics, particularly in learning that requires a deeper understanding of mathematical concepts.